2022
DOI: 10.1021/acsami.2c01406
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dielectric Energy Storage Performance of 0.45Na0.5Bi0.5TiO3-0.55Sr0.7Bi0.2TiO3/AlN 0–3 Type Lead-Free Composite Ceramics

Abstract: Na 0.5 Bi 0.5 TiO 3 (NBT) ceramic is the promising dielectric material for energy storage devices due to its high maximum polarizability and temperature stability. However, its low breakdown strength limits its application. Here, we prepared 0−3 type composite 0.45Na 0.5 Bi 0.5 TiO 3 -0.55Sr 0.7 Bi 0.2 TiO 3 /x wt % AlN (NBT-SBT/xAlN) to increase the breakdown strength. The effects of the various AlN contents on the phase composition, microstructures, dielectric, and energy storage properties of NBT-SBT were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…In the last decade, compared with the normal FE and antiFE (AFE) materials, unceasing efforts focusing on ceramic capacitor materials with relaxor FE (RFE) behavior have been made, especially on ABO 3 perovskite materials. Taking (Bi, K, Na)­TiO 3 -, NaNbO 3 -, and BiFeO 3 -based lead-free ceramics as examples, a breakthrough W r of above 7 J/cm 3 accompanied by η above 69% could be obtained via fine composition control. After doping the second counterparts, an obvious relaxor behavior has been identified, which has been derived from the response of polar nanoregions (PNRs) to an alternating electric field. Specifically, accompanied by the evolution of microdomain to nanosized domains, RFE ceramics could ensure a large Δ P ( P m – P r ) and a moderate E B .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, compared with the normal FE and antiFE (AFE) materials, unceasing efforts focusing on ceramic capacitor materials with relaxor FE (RFE) behavior have been made, especially on ABO 3 perovskite materials. Taking (Bi, K, Na)­TiO 3 -, NaNbO 3 -, and BiFeO 3 -based lead-free ceramics as examples, a breakthrough W r of above 7 J/cm 3 accompanied by η above 69% could be obtained via fine composition control. After doping the second counterparts, an obvious relaxor behavior has been identified, which has been derived from the response of polar nanoregions (PNRs) to an alternating electric field. Specifically, accompanied by the evolution of microdomain to nanosized domains, RFE ceramics could ensure a large Δ P ( P m – P r ) and a moderate E B .…”
Section: Introductionmentioning
confidence: 99%
“…14 In general, grain refinement facilitates a significant enhancement of the breakdown field strength ( E b ) of dielectric ceramics, which results in higher W rec values. 15–18 Moreover, it is a more popular strategy to design RFE materials with nano-sized domains as well as elongated P – E curves and large η by chemical doping. 19–29 Under an applied electric field, nanodomains are easier to reverse than microdomains, leading to the reduction of P r and the enhancement of η .…”
Section: Introductionmentioning
confidence: 99%
“…6–10 A higher energy storage performance (5.59 J cm −3 , 90%) was obtained at 360 kV cm −1 by introducing a second-phase AlN in BNT ceramics. 16 Li et al obtained ultra-high energy storage performance (9.55 J cm −3 , 90%) in (1 − x )(BNT-BT)– x CTT ceramics at 410 kV cm −1 . 10 In general, the dopant causes the weakening of the strong polar phase of the matrix and the generation of the non-polar phase, which can only enhance the polarity and P max at high electric fields, resulting in higher W rec and η .…”
Section: Introductionmentioning
confidence: 99%
“…These ceramics have attracted the interest of scientists around the world. In previous research, the permittivity of ceramic materials was generally positive. In reality, it has been observed that the permittivity could be as well negative. Up to now, negative permittivity generally results from the dielectric resonance of dipoles due to negative phase angle and electromechanical coupling at high frequencies. NBT exhibits a diffuse phase transition nature leading from its nonpolar ferroelectric tetragonal transitions to its ferroelectric rhombohedral transitions. Recently much work involved the enhancement of the electrical properties of (1 – x )­NBT– x KBT by substitutions, investigation of impedance data to differentiate between the bulk contribution (grains) and the influence of the grain boundaries, and identifying the elements which are required for the conduction phenomenon in (1 – x )­NBT– x KBT ceramics at high temperature. , Complex impedance spectroscopy (CIS) can be used as a convenient and useful nondestructive experimental method which allows us to (i) study the physical processes that reveal the electrical and dielectric properties of compounds, (ii) differentiate the contributions of grains and grain boundaries to the transport properties of compounds, (iii) identify the relaxation frequency/the relaxation time of the charge carriers in the material, and (iv) further investigate conductivity, relative permittivity, and dielectric losses versus frequency. , Motivated by the previous consideration, we prepared a (1 – x )­NBT– x KBT system by solid-state reaction method ( x (%) = 0, 12, 16, 20, 30, and 100) with compositions close to MPB. This study aims to examine in detail the influence of the addition of KBT on the generation mechanism of negative permittivity behavior, as well as the impedance and conductivity of NBT over a broad range of temperatures and frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, it has been observed that the permittivity could be as well negative. 21 23 Up to now, negative permittivity generally results from the dielectric resonance of dipoles due to negative phase angle and electromechanical coupling at high frequencies. 24 26 NBT exhibits a diffuse phase transition nature leading from its nonpolar ferroelectric tetragonal transitions to its ferroelectric rhombohedral transitions.…”
Section: Introductionmentioning
confidence: 99%